T-cell derived acetylcholine aids host defenses during enteric bacterial infection with Citrobacter rodentium. - Valerie T Ramirez; Dayn R Godinez; Ingrid Brust-Mascher; Eric B Nonnecke; Patricia A Castillo; Mariana Barboza Gardner; Diane Tu; Jessica A Sladek; Elaine N Miller; Carlito B Lebrilla; Charles L Bevins; Melanie G Gareau; et al. (PLoS Pathogens, 2019)
The regulation of mucosal immune function is critical to host protection from enteric pathogens but is incompletely understood. The nervous system and the neurotransmitter acetylcholine play an integral part in host defense against enteric bacterial pathogens. Here we report that acetylcholine producing-T-cells, as a non-neuronal source of ACh, were recruited to the colon during infection with the mouse pathogen Citrobacter rodentium. These ChAT+ T-cells did not exclusively belong to one Th subset and were able to produce IFNγ, IL-17A and IL-22. To interrogate the possible protective effect of acetylcholine released from these cells during enteric infection, T-cells were rendered deficient in their ability to produce acetylcholine through a conditional gene knockout approach. Significantly increased C. rodentium burden was observed in the colon from conditional KO (cKO) compared to WT mice at 10 days post-infection. This increased bacterial burden in cKO mice was associated with increased expression of the cytokines IL-1β, IL-6, and TNFα, but without significant changes in T-cell and ILC associated IL-17A, IL-22, and IFNγ, or epithelial expression of antimicrobial peptides, compared to WT mice. Despite the increased expression of pro-inflammatory cytokines during C. rodentium infection, inducible nitric oxide synthase (Nos2) expression was significantly reduced in intestinal epithelial cells of ChAT T-cell cKO mice 10 days post-infection. Additionally, a cholinergic agonist enhanced IFNγ-induced Nos2 expression in intestinal epithelial cell in vitro. These findings demonstrated that acetylcholine, produced by specialized T-cells that are recruited during C. rodentium infection, are a key mediator in host-microbe interactions and mucosal defenses.